A History of Aesthetics from Homer to Digital Mash-ups: Cumulative Creativity and the Demise of Copyright Exclusivity. (3rd July 2015) - Frosio, Giancarlo F.
Abstract : Under a regime of limited economic incentive for creativity and confined commodification of information, humanity produced the greatest portion of human knowledge. To mention some, the Bible, the Qur'an, the Mahābhārata, the Iliad and Odyssey, the Aeneid, the Scandinavian Sagas, the German Lay of the Nibelungs, the Celtic legends of Arthur, the Romances and Chanson De Geste all came to life well before strong economic rights were attached to creativity. Later, Petrarch declaimed the Dolce Stil Novo, Dante wrote the Divina Commedia, Chaucer fathered English literature, Ludovico Ariosto chanted Orlando Furioso, Cervantes unleashed his Don Quixote de la Mancha against windmills and earlier epic literature, and Shakespeare gave immortal life to the love of Romeo and Juliet . Emulation, imitation, plagiarism, borrowing, remixing and recombination had a constant demiurgic power in the history of creativity. However, modern policies have largely forgotten the cumulative and collaborative nature of creativity. In this article, I highlight shortcomings of the copyright principle of exclusivity by rereading the history of aesthetics at the dawn of the networked age.